Biopolymer production using hydrocarbon-degrading microbial consortia - Bertola, Gonzalo (2022)
Polyhydroxyalkanoates (PHAs) are biodegradable microbial polymers, emerging as an alternative topetroleum-based plastics. The industrial production of PHAs using bacteria is widely studied but less information exists about the production of PHAs using microbial consortia. In order to reduce costs, the utilization of hydrocarbon (HC) wastes may emerge as an interesting option. Wastes such as bilge water from ships, with a high hydrocarbon load, are very abundant in port regions and are often discharged into the sea, polluting its surroundings. The objective of this work was to analyze the production of PHAs and to characterize the biopolymer(s) obtained from HC-biodegrading microbial consortia present in bilge wastes, using them as the carbon source. Bilge consortium (BC) cultures were grown in seawater with the addition of phosphorus and nitrogen. Growth conditions were adjusted by varying various factors, such as culture volume (50, 150ml), bilge concentration (0.25% v/v, 1% v/v, 2% v/v) and nitrogen source, NaNO3 (0.05% m/v, 0.2% m/v). Bacterial growth was determined by OD 600nm. PHAs were extracted by treatment with 1% NaClO and abundance was estimated as percent accumulation. Volumes of 150 ml and bilge concentrations of 0.25% v/v proved to be more practical for testing. Regarding nitrogen concentrations, no significant differences were found for cellular growth or PHAs accumulation, which was around 60% w/w. Simultaneously, the ability of the consortium to degrade total HC was measured. After 7 days of culture, a biological degradation of 74% was determined. Finally, cheese whey 2% v/v was used as a nutrient source simultaneously with the bilge. A higher bacterial growth was achieved, with minimal decrease in the percentage of PHA accumulation. Fluorescence microscopy (staining with Nile Blue) confirmed the presence of PHAs in the aforementioned cultures. The biopolymers obtained will be analyzed for identification. Since a 16S metagenomic analysis of the consortium used was available, an in silico analysis of the main genera identified in the sample (Marinobacter, Alcanivorax and Parvibaculum) was also performed. One or more copies of genes related to PHAs metabolism (phaC, phaP and phaA) were found in all genera present. The results of this work contribute to the knowledge on the production of biopolymers from hydrocarbon wastes by means of microbial consortia, and would help in the future design of bioremediation processes of bilge wastes coupled to the obtaining of value-added products.